1994
DOI: 10.1159/000119528
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current Treatments for Migraine

Abstract: Acute drug therapy is the mainstay of treatment for migraine sufferers, with prophylaxis reserved for those with frequent or severe attacks. The majority of treatments have been in use for many years, although their value is often poorly documented due to a lack of well-controlled trials undertaken with defined diagnostic criteria and study end-points. Analgesics with anti-emetics, nonsteroidal anti-inflammatory drugs and ergot derivatives are used for acute treatment. Recently, the selective 5-HT1 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Retroperitoneal, pleural and cardiac valve fibroses have been reported after prolonged dosing [12]. Oral ergotamine is effective, especially in the prevention of nocturnal attacks [3], but this drug also has a well-known side-effect profile, and there is a danger of dependency [13]. Lithium carbonate has been reported to prevent attacks in 40% of patients and is particularly useful in older patients [14].…”
Section: Management Of Cluster Headachementioning
confidence: 99%
“…Retroperitoneal, pleural and cardiac valve fibroses have been reported after prolonged dosing [12]. Oral ergotamine is effective, especially in the prevention of nocturnal attacks [3], but this drug also has a well-known side-effect profile, and there is a danger of dependency [13]. Lithium carbonate has been reported to prevent attacks in 40% of patients and is particularly useful in older patients [14].…”
Section: Management Of Cluster Headachementioning
confidence: 99%
“…In previous clinical trials, eletriptan has been found to be more effective than sumatriptan and Cafergot® 1 , 2 . This study compared the efficacy and safety of oral eletriptan (40mg) to oral naratriptan (2.5mg) and placebo in treating a single migraine attack.…”
Section: Introductionmentioning
confidence: 98%
“…Eletriptan is a selective 5‐HT 1B/1D agonist previously shown to be effective in the acute treatment of migraine 1 3 . This study investigated the efficacy of eletriptan in a subset of patients from a previous study who discontinued sumatriptan due to lack of response.…”
Section: Introductionmentioning
confidence: 99%